The imperative in natural syntax - Orešnik, Janez (Linguistica (Ljubljana), 2011)
The framework of this paper is Natural Syntax initiated by the author in the tradition of (morphological) naturalness as established by Wolfgang U. Dressler and Willi Mayerthaler. Natural Syntax is a pseudo-deductive linguistic theory, and this is its most recent version. The naturalness judgements are couched in naturalness scales, which follow from the basic parameters (or "axioms") listed at the beginning of the paper. The predictions of the theory are calculated in what are known as deductions, the chief components of each being a pair of naturalness scales and the rules governing the alignment of corresponding naturalness values. Parallel and chiastic alignment is distinguished and related to Henning Andersen's early work on markedness. The basic idea is to illustrate how a (pseudo)deductive theory of syntax performs if it insists on avoiding abstract solutions, and in particular on excluding any generative component. In this paper the framework of Natural Syntax is applied mostly outside its original domain; namely, to the morphological behaviour of the imperative in various languages.
Keywords: impératif; naravna skladnja; skladnja; syntax; syntaxe; syntaxe naturelle; velelnik